Preparation of cobalt sulfide catalyst and application of cobalt sulfide catalyst in preparation of methyl mercaptan by hydrogenation of hydrogen sulfide and carbon dioxide

By preparing CoxSy catalysts with high Co2+/Co3+ ratio and abundant sulfur vacancy, the problem of difficulty in CO2 activation and low conversion rate of H2S and CO2 reactions was solved, and the effect of efficient catalyzing the formation of methylmercaptan in H2S and CO2 was achieved.

CN119869562AActive Publication Date: 2025-04-25FUZHOU UNIV

Patent Information

Application Number
CN202510123989.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-25
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

In the prior art, CO2 is difficult to activate and the low conversion rate of methylmercaptan reaction with CO2 is caused.

Method used

Using a preparation method of CoxSy catalyst, a catalyst with a high Co2+/Co3+ ratio and rich sulfur vacancy was prepared by stirring the cobalt source and the sulfur source in a solvent to react with hydrothermal heat, thereby improving the reaction activity.

Benefits of technology

The conversion rate of H2S and CO2 to form methyl mercaptan is improved. The catalyst has a high specific surface area and exposes more active sites, achieving a highly efficient catalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869562A_ABST
    Figure CN119869562A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a CoxSy catalyst, and belongs to the technical field of catalyst preparation. According to the method, the morphology of CoxSy is regulated and controlled by using different solvents, so that four CoxSy catalysts with different morphology characteristics are synthesized. The catalyst is simple in preparation method and high in repeatability. The obtained CoxSy catalyst has a high specific surface area, more active sites can be exposed, reaction raw materials are in full contact with the active sites of the catalyst, and meanwhile, the catalyst has relatively high sulfur tolerance and rich sulfur vacancies, and is beneficial to adsorption and activation of H2S and CO2. Therefore, the obtained CoxSy catalyst shows high catalytic activity in a reaction for preparing methyl mercaptan through H2S and CO2 hydrogenation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of an environmental catalyst and its application field, and in particular to a Co x S y A method for preparing a catalyst and its application in hydrogenating H2S and CO2 to produce methyl mercaptan. Background Art

[0002] Production processes such as oil refining and coal chemical industry not only emit H2S gas, but also produce a large amount of CO2. H2S can seriously corrode production equipment and poison catalysts. CO2 can cause environmental problems such as global warming. Therefore, H2S pollution control and CO2 emission reduction are imperative. Among various sulfur-containing chemicals, methyl mercaptan (CH3SH) can be used as an important organic synthesis intermediate, and is often used to prepare chemical products such as lysine protein, chloramine insecticide, wool dyeing auxiliaries, gas odorizers, and fragrances. It has a wide range of applications. However, the process of producing methyl mercaptan in my country is immature, especially the lack of low-cost green and clean production technology. The domestic methyl mercaptan production capacity lags behind, the market gap is large, and it relies on imports. Therefore, the one-step synthesis of methyl mercaptan using H2S and CO2 as raw materials can not only convert H2S and CO2 at the same time, but also obtain high value-added products. It has the advantages of easy availability of raw materials and significant prospects for industrial application, which can maximize the utilization of resources.

[0003] At present, the mainstream process routes for synthesizing methyl mercaptan are methanol mercaptanation and high-sulfur syngas (H2S / CO / H2). Methanol mercaptanation is a relatively mature commercial technology, but it consumes a lot of energy and equipment and produces a large amount of acidic gas CO2, which is not conducive to the ecological environment. The high-sulfur syngas method has attracted much attention for its advantages such as high atomic utilization, simple process, and low production equipment cost. On this basis, replacing CO with CO2, that is, preparing methyl mercaptan with H2S, CO2 and H2 as raw materials, can not only reduce greenhouse gases, but also achieve the purpose of synchronous conversion and utilization of acidic gas H2S. Summary of the invention

[0004] The purpose of the present invention is to provide a Co x S y The invention discloses a method for preparing a catalyst and its application, so as to solve the problems in the prior art that CO2 is difficult to activate and the conversion rate of methyl mercaptan generated by the reaction of H2S and CO2 is low. x S y The catalyst has a spherical morphology composed of small particles, which has a higher Co 2+ / Co 3+ The high specific surface area and abundant sulfur vacancies can improve the reaction activity, and the higher specific surface area exposes more active sites, thus efficiently catalyzing the reaction of H2S and CO2 to produce methyl mercaptan.

[0005] To achieve the above object, the present invention adopts the following technical solution: A kind of Co x S y The catalyst, the preparation method of which comprises the following steps: 1) Add the cobalt source to the solvent, continue stirring for half an hour, and then allow to stand or undergo solvothermal reaction to obtain a precursor; 2) mixing the obtained precursor with a sulfur source and stirring for half an hour, and then performing a hydrothermal reaction; 3) After the reaction temperature drops to room temperature, the obtained precipitate is filtered, washed, and dried to obtain the Co x S y catalyst; Where x is an integer from 1 to 9, and y is an integer from 1 to 8.

[0006] Furthermore, the cobalt source in step 1) is cobalt nitrate hexahydrate (Co(NO3)2·6H2O) or cobalt chloride hexahydrate (CoCl2·6H2O), preferably cobalt nitrate hexahydrate.

[0007] Furthermore, the solvent in step 1) is one or more of water, methanol, isopropanol and glycerol, preferably isopropanol and glycerol (V 异丙醇 :V 甘油 =4:1) mixed solution.

[0008] Furthermore, the standing time in step 1) is 0 to 24 hours.

[0009] Furthermore, the temperature for the solvothermal reaction in step 1) is 180° C., and the time is 2 to 5 hours, preferably 3 hours.

[0010] Furthermore, in step 1), 2-methylimidazole or the like may be further added as a template agent to carry out the reaction.

[0011] Furthermore, in step 2), the sulfur source is thiourea or thioacetamide, preferably thiourea.

[0012] Furthermore, the temperature of the hydrothermal reaction in step 2) is 120° C. to 180° C., and the time is 8 to 24 hours, preferably 12 hours.

[0013] Furthermore, the filtering and washing in step 3) is performed by washing with deionized water and ethanol three times in turn.

[0014] Furthermore, the drying in step 3) is performed by vacuum drying at a temperature of 80°C.

[0015] The catalyst prepared by the above method is a petal-shaped Co x S y, spherical particles of Co x S y , regular polygonal Co x S y Or stacked tower Co x S y , which can all be used in the reaction of hydrogen sulfide and carbon dioxide hydrogenation to produce methyl mercaptan.

[0016] Furthermore, in the reaction, the raw gas contains 1% CO2, 4% H2S, 4% H2 and balance gas N2; the raw gas flow rate is 5 mL / min; the reaction pressure is 1.5 Mpa; and the reaction temperature is 200~360 ℃, preferably 280 ℃.

[0017] The present invention has the following advantages and beneficial effects: 1. Co prepared by the present invention x S y The catalyst has abundant sulfur vacancies, which can promote the adsorption of H2S and CO2 and improve the reaction activity. In addition, its raw materials are cheap and the preparation process is simple, so it has broad application prospects.

[0018] 2. Co synthesized by the present invention x S y The catalyst has a higher specific surface area, which can expose more active sites. x S y The catalyst has good activity in the study of catalytic hydrogenation of H2S and CO2 to methyl mercaptan. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Co prepared in Examples 1 to 4 x S y X-ray powder diffraction spectrum of the catalyst.

[0020] Figure 2 Co prepared in Examples 1 to 4 x S y SEM images of the catalyst (A~D correspond to Co x S y -A~Co x S y -D).

[0021] Figure 3 Co prepared in Example 2 x S y -Transmission electron microscopy image of catalyst B.

[0022] Figure 4 Co prepared in Examples 1 to 4 x S y XPS spectrum of the catalyst.

[0023] Figure 5 Co prepared in Examples 1 to 4 x S y N2 adsorption-desorption isotherms of the catalyst.

[0024] Figure 6 Co prepared in Examples 1 to 4 x S y EPR spectrum of the catalyst.

[0025] Figure 7 Co prepared in Examples 1 to 4 x S y Comparison of catalytic activity of catalysts in the hydrogenation of H2S and CO2 to produce methyl mercaptan. DETAILED DESCRIPTION

[0026] A kind of Co x S y The method for preparing a catalyst comprises the following steps: 1) Add the cobalt source to the solvent, continue stirring for half an hour, then let it stand for 0 to 24 hours, or pour it into a hydrothermal kettle and react at 180°C for 2 to 5 hours to obtain a precursor; 2) Mix the obtained precursor with the sulfur source and continue stirring for half an hour, then pour into a hydrothermal reactor and perform hydrothermal reaction at 120℃~180℃ for 8~24 hours; 3) After the reaction, the hydrothermal autoclave was cooled to room temperature, and the obtained precipitate was washed three times with deionized water and ethanol in turn, and then dried in vacuum at 80 °C to obtain the Co x S y Catalyst; wherein x=an integer from 1 to 9, y=an integer from 1 to 8.

[0027] Wherein, the cobalt source in step 1) is cobalt nitrate hexahydrate (Co(NO3)2·6H2O) or cobalt chloride hexahydrate (CoCl2·6H2O). The solvent is one or more of water, methanol, isopropanol and glycerol.

[0028] The sulfur source in step 2) is thiourea or thioacetamide.

[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0030] Example 1 Petal-shaped Co x S y Catalyst preparation Weigh 1 mmol of Co(NO3)2·6H2O and dissolve it in 70 mL of deionized water. Stir continuously at 50 °C for half an hour. Add 6 mmol of thiourea while stirring. Then pour the mixed solution into a 100 mL hydrothermal kettle and react at 180 °C for 12 hours. After the temperature of the hydrothermal kettle drops to room temperature, take out the precipitate, wash it three times with deionized water and ethanol in turn, and then dry it in a vacuum oven at 80 °C. The final product is a petal-shaped mixed phase catalyst of CoS2 and CoS, recorded as Co x S y -A.

[0031] Example 2 Spherical Co particles x S y Catalyst preparation Weigh 1 mmol of Co(NO3)2·6H2O and dissolve it in a mixed solution of 60 mL of isopropanol and 15 mL of glycerol, and stir it continuously for half an hour. Then pour the mixed solution into a 100 mL hydrothermal autoclave and react it at 180 °C for 3 hours. The obtained precipitate is washed three times with deionized water and ethanol in turn, and then placed in a vacuum oven at 80 °C to obtain a precursor. The obtained precursor is dissolved in 50 ml of deionized water, and 0.5 mmol of thiourea is added. After stirring for half an hour, the mixed solution is poured into a 100 mL hydrothermal autoclave and reacted at 180 °C for 12 hours. After the temperature of the hydrothermal autoclave drops to room temperature, take out the precipitate, wash it three times with deionized water and ethanol in turn, and then place it in a vacuum oven at 80 °C to dry. The final product is a spherical Co9S8 catalyst, recorded as Co x S y -B.

[0032] Example 3 Regular polygonal Co x S y Catalyst preparation Weigh 2 mmol of Co(NO3)2·6H2O and dissolve it in 90 mL of anhydrous methanol. Weigh 1 mmol of 2-methylimidazole as a template and dissolve it in 30 mL of methanol solution. Then quickly pour the latter solution into the former solution. After continuous stirring for half an hour, let the mixed solution stand at room temperature for 24 hours. Then centrifuge and wash the solution after standing to obtain a precursor. Dissolve the obtained precursor in 40 mL of anhydrous ethanol, add 0.1 mol of thiourea and continue stirring for half an hour. Pour the mixed solution into a 100 mL hydrothermal kettle and react at 120 °C for 4 hours. After the temperature of the hydrothermal kettle drops to room temperature, take out the precipitate, wash it three times with deionized water and ethanol in turn, and then dry it in a vacuum oven at 80 °C. The final product is a regular polygonal Co3S4 catalyst, recorded as Co x Sy -C.

[0033] Example 4 Stacked Tower Co x S y Catalyst preparation Weigh 1 mmol of Co(NO3)2·6H2O and dissolve it in 70 mL of deionized water. Stir continuously at 50 °C for half an hour. Add 6 mmol of thioacetamide while stirring. Then pour the mixed solution into a 100 mL hydrothermal kettle and react at 180 °C for 12 hours. After the temperature of the hydrothermal kettle drops to room temperature, take out the precipitate, wash it three times with deionized water and ethanol in turn, and then dry it in a vacuum oven at 80 °C. The final product is a stacked tower-shaped CoS catalyst, recorded as Co x S y -D.

[0034] Preparation of Comparative Example MoS2 Catalyst 3 mmol of ammonium molybdate tetrahydrate and 126 mmol of thiourea were dissolved in 120 mL of deionized water and stirred for 15 min. The mixed solution was then poured into a 100 mL hydrothermal reactor and reacted at 180 °C for 12 hours. After the temperature of the hydrothermal reactor dropped to room temperature, the precipitate was taken out and washed three times with deionized water and ethanol in turn, and then dried in a vacuum oven at 80 °C to obtain the MoS2 catalyst.

[0035] X-ray powder diffraction (XRD): The phase characterization of the samples was measured using Panalytical's X'pert pro powder diffractometer, with an X'celerator as the detector, a copper target (Cu Kα, λ = 0.154 nm) as the excitation radiation source, an operating voltage of 45 KV, and an operating current of 40 mA.

[0036] The morphology of the catalyst was observed by S-4800 field emission scanning electron microscope. The vacuum degree of the analysis chamber was less than 2.7×10 –6 Pa, the scanning voltage and current were 5 kV and 7 μA respectively. The sample powder was glued to the conductive glue and then observed after gold spraying.

[0037] Field emission transmission electron microscopy (TEM): TEM images of the samples were observed on a Tecnai G2 F20 transmission electron microscope (TEM) with an accelerating voltage of 200 KV.

[0038] X-ray Photoelectron Spectroscopy (XPS): The elemental chemical state of the sample surface is characterized by using the ESCACAB 250xi X-ray Photoelectron Spectrometer, and the emission source is a monochromatic A1 Kα excitation source (1486.6 eV, 15 kV, 10.8 mA). First, the sample is pressed and fixed on an ultra-high vacuum insulating tape, and the tape is pasted on the sample holder. Before entering the analysis room, the sample injection room and sample preparation room are gradually drawn to the specified vacuum degree. The vacuum degree in the analysis chamber is less than 10 -8 bar, characterizing the elemental chemical state of the catalyst. The obtained spectrum was calibrated with C1s=284.8 eV as the internal standard.

[0039] N2 physical adsorption (N2Physisorption) was used to analyze the specific surface area of ​​the sample using a fully automatic specific surface area analyzer (MicrometricASAP2020). The test conditions were: weigh 0.1 g of sample, pre-treat at 200 °C for 120 min, and then analyze and test at liquid nitrogen temperature. The specific surface area of ​​the sample was calculated according to the BJH method.

[0040] The defect information of the sample can be obtained by E-500 electron paramagnetic resonance instrument (Bruker). The test is carried out at a low temperature of -150°C and a test frequency of 100 kHz. After the sample is placed in the quartz test tube, the test tube should be kept vertical, and the working environment of the instrument should be stable and the air should be circulated.

[0041] Figure 1 Co prepared in Examples 1 to 4 of the present invention x S y X-ray powder diffraction spectrum of the catalyst. It can be seen from the figure that the sample Co x S y -A's diffraction peaks are attributed to CoS2 (JCPDS 89-1492) and CoS (JCPDS 75-0605); x S y -B's diffraction peak is attributed to Co9S8 (JCPDS 73-1442); sample Co x S y The diffraction peak of -C is attributed to Co3S4 (JCPDS 42-1448); x S y The diffraction peak of -D is attributed to CoS (JCPDS 75-0605).

[0042] Figure 2 Co prepared in Examples 1 to 4 x S y SEM image of the catalyst. It can be seen from the figure that Co x Sy -A is a petal-like morphology composed of 200nm nanosheets, and the diameter of the petals is about 7 μm (A). x S y -B is a spherical morphology composed of 70 nm nanoparticles, and the diameter of the spherical particles is about 4 μm (B). x S y -C is a regular cubic morphology with a side length of 400 nm (C). x S y -D is a tower-like morphological feature composed of irregular polygons (D).

[0043] Figure 3 The spherical Co particles prepared in Example 2 x S y TEM image of -B catalyst. It can be seen from the figure that it is composed of solid small particles, in which the lattice fringes correspond to XRD, and the (311) crystal plane of Co9S8 can be seen.

[0044] Figure 4 Co prepared in Examples 1 to 4 x S y XPS spectrum of the catalyst. As can be seen from the figure, the peak positions of the four samples are 778.4 eV, 793.4 eV, 781.7 eV, 798.1 eV, 786.2 eV, and 802 eV, which are respectively attributed to Co 3+ 、Co 2+ and satellite peaks. By comparing the peak intensities, it is found that Co 2+ / Co 3+ The values ​​from large to small are Co x S y -B>Co x S y -C>Co x S y -D>Co x S y -A. Since it is known that Co 2+ / Co 3+ The ratio is positively correlated with the activity, and its active site is Co 2+ , therefore, more Co 2+ It can promote the adsorption and further conversion of H2S and CO2.

[0045] Figure 5 Co prepared in Examples 1 to 4 x S y Physical adsorption and desorption results of the catalyst. It can be seen from the figure that the specific surface areas of the catalysts prepared in Examples 1 to 4 are 8.9 m2 / g, 28.2m 2 / g, 70.4m 2 / g, 14.1 m 2 / g, of which Co x S y -B has a large specific surface area, which can fully expose its active sites and is conducive to the catalytic reaction.

[0046] Figure 6 Co prepared in Examples 1 to 4 x S y EPR spectrum of the catalyst. As can be seen from the figure, the catalyst Co x S y There is a peak at g=2.003, indicating that the catalyst containing sulfur vacancies was successfully synthesized. The presence of sulfur vacancies can improve the reaction activity.

[0047] Performance test of hydrogen sulfide and carbon dioxide hydrogenation to produce methyl mercaptan: The catalysts prepared in Examples 1 to 4 and the comparative example were ground into powders for the activity evaluation of hydrogenation of H2S and CO2 to methyl mercaptan. The test conditions are as follows: the amount of catalyst is 1 g; the raw gas contains 1% CO2, 4% H2S, 4% H2 and balance gas N2; the pretreatment is carried out at 200 °C, the flow rate is 30 mL / min, and the raw gas flow rate during the reaction is 5 mL / min; the reaction pressure is 1.5 MPa; the analysis is carried out using a GC-9790Plus gas chromatograph; the reaction temperature is 200~360 °C.

[0048] Figure 7 The catalytic activity comparison diagram of Examples 1 to 4 in the reaction of hydrogenating H2S and CO2 to produce methyl mercaptan. As can be seen from the figure, the CO2 conversion rate and CH3SH yield of the catalyst are Co x S y -B>Co x S y -C>Co x S y -D>Co x S y -A. Co x S y -B has high catalytic activity because it can produce more sulfur vacancies and has a higher specific surface area, exposing more active sites, promoting the reaction and improving the reaction activity.

[0049] Table 1 is the Co prepared in Examples 1 to 4 x S y Catalytic activity results of the MoS2 catalyst prepared in the comparative example in the hydrogenation of H2S and CO2 to produce methyl mercaptan.x S y -B has significantly higher activity than the control.

[0050] Table 1 Catalytic activity of Examples 1 to 4 and Comparative Examples at 280°C

[0051] In summary, the four different morphologies of Co prepared in the present invention x S y The catalysts have different catalytic performances in the hydrogenation of H2S and CO2 to produce methyl mercaptan. x S y -B sample has the highest catalytic activity and has great application potential.

[0052] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A kind of Co x S y The method for preparing a catalyst is characterized by: The following steps are involved: 1) Add the cobalt source to the solvent, continue stirring for half an hour, and then stand or perform solvent thermal treatment to obtain a precursor; 2) mixing the obtained precursor with a sulfur source and stirring for half an hour, and then performing a hydrothermal reaction; 3) After the reaction temperature drops to room temperature, the obtained precipitate is filtered, washed, and dried to obtain the Co x S y catalyst.

2. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: The cobalt source in step 1) is cobalt nitrate hexahydrate or cobalt chloride hexahydrate.

3. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: The solvent in step 1) is one or more of water, methanol, isopropanol and glycerol.

4. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: In step 1), the standing time is 0 to 24 hours; the temperature for the solvothermal reaction is 180° C., and the time is 2 to 5 hours.

5. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: In step 1), a template agent is also added.

6. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: The sulfur source in step 2) is thiourea or thioacetamide.

7. A Co according to claim 1 x S y The method for preparing a catalyst is characterized by: The temperature of the hydrothermal reaction in step 2) is 120°C to 180°C, and the time is 8 to 24 hours.

8. A Co prepared by the method of claim 1 x S y A catalyst, characterized in that The obtained catalyst is a petal-shaped Co x S y , spherical particles of Co x S y , regular polygonal Co x S y Or stacked tower Co x S y , where x is an integer from 1 to 9, and y is an integer from 1 to 8.

9. A Co as claimed in claim 8 x S y The application of the catalyst is characterized by: The Co x S y The catalyst is used in the reaction of hydrogen sulfide and carbon dioxide to produce methyl mercaptan.

10. A Co according to claim 9 x S y The application of the catalyst is characterized by: The raw gas contains 1% CO2, 4% H2S, 4% H2 and balance gas N2; the raw gas flow rate is 5 mL / min; the reaction pressure is 1.5 Mpa; and the reaction temperature is 200~360 ℃.

Citation Information

Patent Citations

  • Catalyst for synthesizing methyl mercaptan from high-sulfur synthetic gas and preparation method thereof

    CN102600859A

  • Catalyst for synthesis of methyl mercaptan and preparation and application methods of catalyst

    CN113398918A

  • Catalyst for synthesizing methyl mercaptan from carbon dioxide, hydrogen sulfide and hydrogen as well as preparation method and application of catalyst

    CN114308080A

  • Preparation method and application of cobalt sulfide catalyst capable of efficiently activating PMS

    CN116273065A

  • Molybdenum disulfide / zirconium oxide composite catalyst and preparation and application thereof

    CN118022779A

Cited By

  • Preparation method and preparation device of mercaptan

    CN121202739A

  • Process for preparing mercaptans and apparatus therefor

    CN121202739B